In vitro effects of antidepressant drugs on polymorphonuclear leukocyte functions of healthy volunteers [Antidepresan İlaç ve Kombinasyonlarının İnsan Polimorf Nüveli Lökosit Fonksiyonları Üzerine in Vitro Etkisi] - (:unkn) unknown (Turkish Pharmacists Association, 2009)
In our study the effects of the antidepressant drugs buspirone (0.0025/μg/ml), sertraline (0.19/μg/ml), citalopram (0.286/μg/ml, 0.502/μg/ml, 0.703/μg/ml) and fluoxetine (0.015/μg/ml, 0.035/μg/ml, 0.055/μg/ml) on polymorphonuclear leukocyte (PMN) function of 20 healthy young volunteers, whose mean age was 25 were investigated in vitro. PMNs (l×l07cell/ml) were isolated by ficoll-hypaque gradient centrifugation method from venous blood with EDTA. Phagocytosis and intracellular killing activity were assayed by modifying Alexander's method. Fluoxetine at 0.035/μg/ml concentration has significantly increased the PMN's phagocytic activity, of the healthy young volunteers but did not effect their PMN's intracellular killing activity. The results might bring a new immunotherapeutic approach to the therapy of the major depressant patients whose immune system is suppressed.
Keywords: Antidepressant drugs; Intracellular killing activity; Phagocytosis; Polymorphonuclear leukocyte